SEPT6_TRIM33 Gene Fusion and Mutated TP53 Pathway Associate With Unfavorable Prognosis in Patients With B-Cell Lymphomas - Fu, Haiying; Zhou, Huarong; Qiu, Yanyan; Wang, Jianfei; Ma, Zhiming; Li, Hongping; Zhang, Feng; Qiu, Chenxi; Shen, Jianzhen; Liu, Tingbo (Frontiers in Oncology, 2021)
Background: Mounting studies have sought to identify novel mutation biomarkers having diagnostic and prognostic potentials. Nevertheless, the understanding of the mutated pathways related to development and prognosis of B-cell lymphoma is still lacking. We aimed to comprehensively analyze the mutation alterations in genes of canonical signaling pathways and their impacts on the clinic outcomes of patients with B-cell lymphoma. Methods: cfDNA samples from 79 patients with B-cell lymphomas were used for targeted sequencing with a 560-gene panel for depicting mutation landscapes and identifying gene fusion events. The associations of mutation status of genes and seven canonical oncogenic pathways with progression-free survival (PFS) were assessed using Kaplan-Meier test and multivariate Cox analysis. The variant allele frequencies (VAFs) of genes in TP53 and Hippo pathways in paired baseline and post-treatment samples from 18 B-cell lymphoma patients were compared. Results: We detected five fusion genes in at least two patients with B-cell lymphoma, and among them, TCF7L2_WT1 gene fusion was most frequently detected in 30.4% of patients (24 of 79 cases). SEPT6_TRIM33 gene fusion, mutated TP53 and Hippo pathways were significantly associated with poor PFS. Moreover, SEPT6_TRIM33 fusion gene and mutated TP53 pathway were independent prognostic factors for B-cell lymphoma. A decreased VAF of TP53 p.Y88C and LATS2 p.F972L was detected in patients with complete response to treatments. Conclusions: SEPT6_TRIM33 gene fusion and mutated TP53 and Hippo pathways may serve as prognostic makers for B-cell lymphoma patients.